Development of SSCS Based Material of Biological Diversity to Improve Critical Thinking Ability - Aurilia Hakim, Tri; Marianti, Aditya; Widiyaningrum, Priyantini (Journal of Innovative Science Education, 2020)
The rapid development of science and knowledge in the 21st century raises competition from each country to create various innovations in various fields. To meet these challenges are those who have the ability to think critically, logically, systematically, and creatively in order to be able to survive and compete globally. This study aims to analyze the development of SSCS-based worksheets on biodiversity materials including syllabus, lesson plans, worksheets, and evaluation tools on students' critical thinking skills (CBC). The learning model used in this study is Search, Solve, Create, and Share (SSCS). The study was conducted at MAN 1 Brebes class X. Samples were taken using a purposive sampling method consisting of 3 classes with a total of 105 students. This study uses R&D research methods with one group pretest-posttest design. Based on the analysis results obtained an average critical thinking ability of students of 86% complete and 14% of incomplete by obtaining an average N-Gain score of 0.6 in the medium category. Furthermore, the average score of pretest-posttest and N-Gain per KBK indicator has quite a small comparison. These results indicate that the development of SSCS-based worksheets is effective against students' critical thinking skills.